Searches for pair production of third-generation squarks in root s=13 TeV pp collisions - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (European Physical Journal C, 2017)
Searches are presented for direct production oftop or bottom squark pairs in proton–proton collisions at theCERN LHC. Two searches, based on complementary tech-niques, are performed in all-jet final states that are character-ized by a significant imbalance in transverse momentum. Anadditional search requires the presence of a charged leptonisolated from other activity in the event. The data were col-lected in 2015 at a centre-of-mass energy of 13 TeV with theCMS detector and correspond to an integrated luminosity of2.3 fb−1. No statistically significant excess of events is foundbeyond the expected contribution from standard model pro-cesses. Exclusion limits are set in the context of simplifiedmodels of top or bottom squark pair production. Models withtop and bottom squark masses up to 830 and 890 GeV, respec-tively, are probed for light neutralinos. For models with topsquark masses of 675 GeV, neutralino masses up to 260 GeVare excluded at 95% confidence level.